1995
DOI: 10.1126/science.270.5241.1502
|View full text |Cite
|
Sign up to set email alerts
|

Essential Ca 2+ -Binding Motif for Ca 2+ -Sensitive Inactivation of L-Type Ca 2+ Channels

Abstract: Intracellular calcium (Ca2+) inhibits the opening of L-type (alpha 1C) Ca2+ channels, providing physiological control of Ca2+ entry into a wide variety of cells. A structural determinant of this Ca(2+)-sensitive inactivation was revealed by chimeric Ca2+ channels derived from parental alpha 1C and alpha 1E channels, the latter of which is a neuronal channel lacking Ca2+ inactivation. A consensus Ca(2+)-binding motif (an EF hand), located on the alpha 1C subunit, was required for Ca2+ inactivation. Donation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
198
5

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(219 citation statements)
references
References 36 publications
16
198
5
Order By: Relevance
“…34,46 Such a direct binding of Ca 2ϩ ions has been proposed by Gutnick et al 17 for molluscan Ca 2ϩ channels. de Leon et al 11 and Imredy and Yue 23 have recently provided evidence for such a direct effect on native and artificially expressed cardiac L-type Ca 2ϩ channels, and similar mechanisms may also exist in neuronal Land N-type Ca 2ϩ channels. In summary, our results provide strong evidence against the involvement of CaN in the inactivation process of L-and N-type Ca 2ϩ channels, and support the dominant role of direct binding of Ca 2ϩ ions to the channels.…”
Section: Discussionmentioning
confidence: 96%
“…34,46 Such a direct binding of Ca 2ϩ ions has been proposed by Gutnick et al 17 for molluscan Ca 2ϩ channels. de Leon et al 11 and Imredy and Yue 23 have recently provided evidence for such a direct effect on native and artificially expressed cardiac L-type Ca 2ϩ channels, and similar mechanisms may also exist in neuronal Land N-type Ca 2ϩ channels. In summary, our results provide strong evidence against the involvement of CaN in the inactivation process of L-and N-type Ca 2ϩ channels, and support the dominant role of direct binding of Ca 2ϩ ions to the channels.…”
Section: Discussionmentioning
confidence: 96%
“…18 It was hypothesized that CALP2, as a CaM antagonist, opens calcium channels in airway epithelial cells, leading to calcium influx in these cells. 18,53,54 Therefore, we now postulate that the production of radicals by CALP2 in macrophages is predominantly due to an increase of [Ca 2 þ ] i . Although less than in the presence of extracellular calcium, we found that macrophages still produce radicals upon stimulation with CALP2 in calcium-free medium.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, it was hypothesized that the Ca 2ϩ binding to the EF hand in PC-2 (amino acids 754 -782), as well as in the structurally related PCL and ␣ subunit of voltage-activated Ca 2ϩ channels, was the mediator of the Ca 2ϩ -dependent modulation of channel activity (2,33,34). Although studies have not directly addressed this in PC-2, in both polycystin-␣-like and the ␣ 1c voltage-activated Ca 2ϩ channel, this hypothesis has not been entirely borne out (33,35).…”
Section: Discussionmentioning
confidence: 99%